Latin American Immigration, Maternal Education, and Approaches to Managing Children’s Schooling in the United States - Crosnoe, Robert (J Marriage Fam, 2015)
Concerted cultivation is the active parental management of children’s educations that, because it differs by race/ethnicity, nativity, and socioeconomic status, plays a role in early educational disparities. Analyses of the Early Childhood Longitudinal Study–Kindergarten Cohort (n = 10,913) revealed that foreign-born Latina mothers were generally less likely to engage in school-based activities, enroll children in extracurricular activities, or provide educational materials at home when children were at the start of elementary school than were U.S.-born White, African American, and Latina mothers, in part because of their lower educational attainment. Within the foreign-born Latina sample, the link between maternal education and the three concerted cultivation behaviors did not vary by whether the education was attained in the United States or Latin America. Higher maternal education appeared to matter somewhat more to parenting when children were girls and had higher achievement.